(3GdbjhO GdhGQOI Ydi Mb GdedcjI ddeUdMI GdNGUI (B: s (3OQGSI ebGQfI ai GdTQjYI GdESdGejI (B/ s - (3efUhQ UGHQ YHOg NdjaIs; (3Ydj MSjf fLjOIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2011)
(3Ef GdEfSGf eLHhd Ydi MH GdJedc h gh jJUQa aj edcg HMQjI ef GSJYeGd h GSJZdGd h JUQa (B: (3h gPg GdMQjI bO JDOi MJeG Edi EdMGb GdVQQ HGdCNQjf ; acGf dGHO ef JTQjY jMO ef gOg GdMQjI h jbjO Jdc GdJUQaGJ (B: (3ajLYd ddedcjI hXjaI GLJeGYjI (B: (3h bO YQaJ Jdc GdbjhO GdJj aQVgG GdeTQY YfO GSJYeGd Mb GdedcjI h GSJZdGdgG h GdJUQa ajgG HbjhO GdedcjI GdebQQI ddeUdMI GdNGUI h fXQG dCf GdEfSGf GLJeGYj HWHYg h dG jecf Cf jYjT efYRdG dfaSg ; acGf dGHO ef EXgGQ Jdc GdbjhO h JeMjUgG ; djYQa cd eGdc eG dg ef Mbhb h eG Ydjg ef hGLHGJ JLGg LGQgMbhb heG Ydjg ef hGLHGJ JL`Gg LGQg,aL`G J GdJT`QjYGJ dJfX`je Jd`c GdYGdb`I H`jf GdeGd`c hLjQGfg hJM`O e`f MQj`I JU`Qa GdeGd`c a`j edc`g He`G jb`je GdJ`hGRf GdeWd`hH H`jf MQjI GdTNU aj GdJUQa aj edc`g hH`jf a`Qd Gdbj`hO Yd`i g`Pg GdMQj`I MaGX`kG Yd`i eUdMI GdLeGYI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2011.s
(3HHdjhLQGajG(B: (3UaMGJ (B457-477.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJCejf ef GdeSDhdjI ddegfOSjf hGdebGhdjfs; (3GdbGfhf GdeOfjs; (3Mb GdJUQas; (3GdTQjYI GdESdGejIs; (3Gdabgs; (3GdTQjYI h GdbGfhfs; (3GdbjhO GdhGQOIs; (3bjhO GdedcjI GdNGUIs; (3TQW GdefY ef GdJUQas; (3GdJdGUb ai GdLhGQs; (3Mbhb GdGQJaGbs; (3Mb GdGSJYeGds; (3Mb GdGSJZdGds; (3eVGQ GdLhGQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs